2015
DOI: 10.4103/0259-1162.159771
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pneumoperitoneum and Trendelenberg position on oropharyngeal sealing pressure of I-gel™and ProSeal LMA™ in laparoscopic gynecological surgery: A randomized controlled trial

Abstract: Background:A sustained and effective oropharyngeal sealing with supraglottic airway (SGA) is required to maintain the ventilation during laparoscopic gynecological surgery in the Trendelenburg position. This study was conducted with I-gel™ and ProSeal LMA™, two prototype SGA devices with a gastric access.Materials and Methods:We enrolled 60 American Society of Anesthesiologists physical status I and II patients and randomized to either I-gel or ProSeal LMA (PLMA) group. After induction of anesthesia using a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…After the creation of a pneumoperitoneum, minute ventilation needs to be increased in order to maintain an acceptable level of arterial partial pressure of carbon dioxide. The abdominal splinting effect of the pnemonperitoneum reduces thoracic compliance and can lead to increase in airway pressures well in excess of 20 cmH 2 O [7]. The rise of airway pressure consequently inducing air leak from the SADs, might excessively insufflate the stomach and cause aspiration of regurgitated contents.…”
Section: Introductionmentioning
confidence: 99%
“…After the creation of a pneumoperitoneum, minute ventilation needs to be increased in order to maintain an acceptable level of arterial partial pressure of carbon dioxide. The abdominal splinting effect of the pnemonperitoneum reduces thoracic compliance and can lead to increase in airway pressures well in excess of 20 cmH 2 O [7]. The rise of airway pressure consequently inducing air leak from the SADs, might excessively insufflate the stomach and cause aspiration of regurgitated contents.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that it may be because of the increase in intra-abdominal pressure leading to upward movement of trachea, in an LMA which is already placed and fixed. 10 In our study, of 30 cases in group PLMA, none had incidence of sore throat. Of 30 cases studied in group ETT, two cases (6.7%) had incidence of sore throat and blood staining of device way Pressures never crossed the sealing pressure.…”
Section: Discussionmentioning
confidence: 41%
“…OPLP observed in our study was similar to the values noted in earlier studies. 5,9,[14][15][16] There have been many studies comparing PLMA with other SADs like LMA-Supreme and Igel 17,[18][19][20] They have found that both of these devices are suitable alternatives in laparoscopic surgeries, but PLMA has higher OPLP compared to other SADs. Therefore PLMA may be the most suited device for laparoscopic surgeries among SADs.…”
Section: Discussionmentioning
confidence: 99%